Polymerase chain reaction test for detection of SARS-CoV-2 virus and variants - Peshnachka, Aneta; Boshevska, Golubinka; Velichkova, Nevenka; Jancheska, Elizabeta; Vukovikj, Maja; Buzharova, Teodora; Nikolovska, Gordana; Preshova, Ardian; Memeti, Shaban (Scientific Foundation SPIROSKI, 2022)
The first human cases of coronavirus disease (COVID-19), a disease caused by the new coronavirus, was reported on December 31, 2019 in China for the first time. Тhe virus was named temporarily as 2019 new coronavirus (2019 novel coronavirus-2019 -nCoV), or  finally as SARS-CoV-2. The aim of this paper is to give an overview of the laboratory detection of SARS-CoV-2 virus with reverse transcriptase - polymerase chain reaction (RT-PCR) in real time, as well as detection of viral mutations in the Laboratory for virology at the Institute of Public Health. The samples used in the study were taken from all geographical regions in North Macedonia, including the 10 regional Centers for Public Health throughout the country, from hospital patients, from COVID19 hospitals across the country and from the COVID19 checkpoint at the Institute of Public Health. All samples were tested using RT-PCR in real time. Additional assays were applied for identification of the circulating variants. The continuous surveillance of the variants of concern (VOC), as well as the newly emerged variants can allow the public health officials to modify their approach to disease control and management and intervene more effectively as well as in a timely manner in order to prevent major morbidity and mortality from COVID-19.